White collar-1, a central regulator of blue light responses in Neurospora, is a zinc finger protein. - Ballario, P (1996)
The Neurospora crassa blind mutant white collar-1 (wc-1) is pleiotropically defective in all blue light-induced phenomena, establishing a role for the wc-1 gene product in the signal transduction pathway. We report the cloning of the wc-1 gene isolated by chromosome walking and mutant complementation. The elucidation of the wc-1 gene product provides a key piece of the blue light signal transduction puzzle. The wc-1 gene encodes a 125 kDa protein whose encoded motifs include a single class four, zinc finger DNA binding domain and a glutamine-rich putative transcription activation domain. We demonstrate that the wc-1 zinc finger domain, expressed in Escherichia coli, is able to bind specifically to the promoter of a blue light-regulated gene of Neurospora using an in vitro gel retardation assay. Furthermore, we show that wc-1 gene expression is autoregulated and is transcriptionally induced by blue light irradiation.